2002
DOI: 10.1103/physrevd.66.045018
|View full text |Cite
|
Sign up to set email alerts
|

Testing spatial noncommutativity via the Aharonov-Bohm effect

Abstract: The possibility of detecting noncommutative space relics is analyzed using the Aharonov-Bohm effect. We show that, if space is noncommutative, the holonomy receives non-trivial kinematical corrections that will produce a diffraction pattern even when the magnetic flux is quantized. The scattering problem is also formulated, and the differential cross section is calculated. Our results can be extrapolated to high energy physics and the bound θ ∼ [10 TeV] −2 is found. If this bound holds, then noncommutative eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
87
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 44 publications
14
87
1
3
Order By: Relevance
“…This is completely different than in conventional noncommutative quantum mechanics where the differential cross section [16] may depend on theta in the case of small angle. Therefore, the differential cross section for our problem is the same as in the Aharonov-Bohm effect for spin 1/2 particles.…”
Section: Scattering Amplitudementioning
confidence: 93%
See 1 more Smart Citation
“…This is completely different than in conventional noncommutative quantum mechanics where the differential cross section [16] may depend on theta in the case of small angle. Therefore, the differential cross section for our problem is the same as in the Aharonov-Bohm effect for spin 1/2 particles.…”
Section: Scattering Amplitudementioning
confidence: 93%
“…which is the standard result for the Aharonov-Bohm effect (see for example [16]). Therefore, the differential cross section, for a beam polarized parallel to the solenoid direction, the cross section turns out to be…”
Section: Scattering Amplitudementioning
confidence: 99%
“…In literature the NC quantum mechanics and NC quantum field theory have been studied extensively, in literatures many interesting topics of NC quantum theories have been extensively investigated, from the Aharonov-Bohm effect to the quantum Hall effect [1][2][3][4][5][6][7]. Recently quantum theory of NC fields has been proposed as a possible field theory generalization of NC quantum mechanics [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of Zhang [11] have suggested the possibility of testing spatial noncommutativity via cold Rydberg atoms. In Chaichian et al [12], Chaichian et al [13], Falomir et al [14], Li and Dulat [15], Mirza and Zarei [16], Li and Wang [17], Mirza et al [18], Singlton and Vagenas [19], Dulat and Ma [20] and Singleton and Ulbricht [21], the AharonovBohm type phase is studied on a NCS and a NCPS. A lower bound is shown to be 1/ √ θ ≥ 10 −6 GeV for the space noncommutativity parameter in Chaichian et al [12].…”
Section: Introductionmentioning
confidence: 99%